Emerging Evasion Mechanisms of Macrophage Defenses by Pathogenic Bacteria - Leseigneur, Clarisse; Lê-Bury, Pierre; Pizarro-Cerdá, Javier; Dussurget, Olivier (Frontiers in Cellular and Infection Microbiology, 2020)
Macrophages participate to the first line of defense against infectious agents. Microbial pathogens evolved sophisticated mechanisms to escape macrophage killing. Here, we review recent discoveries and emerging concepts on bacterial molecular strategies to subvert macrophage immune responses. We focus on the expanding number of fascinating subversive tools developed by Listeria monocytogenes, Staphylococcus aureus, and pathogenic Yersinia spp., illustrating diversity and commonality in mechanisms used by microorganisms with different pathogenic lifestyles.